Investigating the sustainable digital business models used by social enterprises to address socio-environmental concerns in Malaysia - Mohd Sam, Mohd Fazli; Ismail, Albert Feisal @ Muhd Feisal; Hashim, Nik Mohd Zarifie; Mohd Kasim, Noor Shahida; Mat Isa, Siti Sarah (Research and Scientific Innovation Society, 2025)
The purpose of this study is to investigate the sustainable digital business models that social entrepreneurs use to address socio-environmental concerns in Malaysia. Social enterprises contribute significantly to change by combining business principles with an environmental or social goal. The study focuses on the intersection of digital technology, social entrepreneurship, and sustainable practices to understand how these elements combine to create innovative solutions for Malaysia’s socio-environmental issues. We’ll look at how digital technology can be incorporated into these models to create environmental and social benefits. Data was gathered through interviews, and a few Peninsular, Malaysia-based social entrepreneurs provided genuine information. According to the study’s findings and outcomes, most respondents were driven to use digital platforms or channels to grow their social companies. Through online business, customer engagement, sharing their stories, advertising, and identifying their social mission to address or lessen socioenvironmental issues in Malaysia, these social entrepreneurs, enterprises, or businesses receive much needed community support.